1994
DOI: 10.1021/bi00200a038
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from 18O Exchange Studies for an Exocyclic Methylene Intermediate in the Reaction Catalyzed by T4 Deoxycytidylate Hydroxymethylase

Abstract: 18O exchange experiments were designed to identify the final intermediate in the catalytic mechanism of bacteriophage T4 deoxycytidylate (dCMP) hydroxymethylase (CH). CH catalyzes the formation of 5-(hydroxymethyl)-dCMP (HmdCMP) from dCMP and methylenetetrahydrofolate (CH2-THF). CH resembles thymidylate synthase (TS), an enzyme of known three-dimensional structure, in both amino acid sequence and the reaction catalyzed. The final intermediate in the reaction catalyzed by TS or CH has been proposed to be the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…During the initial steps, they both catalyze the transfer of a methylene group from CH 2 H 4 folate to C-5 of either dCMP or dUMP (Carreras and Santi, 1995; Figure 3). 18 O-exchange studies indicated the existence of a 5-exocyclic methylene intermediate in the reaction mechanism of T4 CH (Butler et al, 1994). The same intermediate was also proposed for TSs (Stroud and Finer-Moore, 1993).…”
Section: Catalysis Of Hydroxymethylation Reactionmentioning
confidence: 76%
“…During the initial steps, they both catalyze the transfer of a methylene group from CH 2 H 4 folate to C-5 of either dCMP or dUMP (Carreras and Santi, 1995; Figure 3). 18 O-exchange studies indicated the existence of a 5-exocyclic methylene intermediate in the reaction mechanism of T4 CH (Butler et al, 1994). The same intermediate was also proposed for TSs (Stroud and Finer-Moore, 1993).…”
Section: Catalysis Of Hydroxymethylation Reactionmentioning
confidence: 76%
“…18 O-exchange experiments have identi®ed the ®nal exocyclic methylene intermediate formed during the proposed mechanism (Butler et al, 1994). Roles in cofactor binding and in catalysis of residues Glu60, Cys148, and Asp179 of T4 CH have been examined by site-directed mutagenesis (Graves et al, 1992;Hardy et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…5hmC in mammalian DNA is produced post-replicatively by the Tet-catalyzed oxidation of 5-methyl cytosine (5mC)34. In T-even phage, the deoxycytidylate (dCMP) hydroxymethylase (CH) transfers the methylene group from methylene-tetrahydrofolate (CH 2 THF) to the C5 atom of dCMP, and then uses solvent water molecule to hydrate the methylene group to generate hydroxymethyl dCMP (hmdCMP)5, a precursor to be incorporated into DNA during replication6. Thereafter, its hydroxymethyl group serves as a substrate for glucosylation to form glucosylhydroxymethylated DNA to avoid cleavage by the host restriction systems78.…”
mentioning
confidence: 99%